UV-B absorbing pigments in spores: biochemical responses to shade in a high-latitude birch forest and implications for sporopollenin-based proxies of past environmental change - Fraser,WT; Sephton,MA; Watson,JS; Self,S; Lomax,BH; James,DI; Wellman,CH; Callaghan,TV; Beerling,DJ (Polar Research, 2011)
Current attempts to develop a proxy for Earth’s surface ultraviolet-B (UV-B) flux focus on the organic chemistry of pollen and spores because their constituent biopolymer, sporopollenin, contains UV-B absorbing pigments whose relative abundance may respond to the ambient UV-B flux. Fourier transform infrared (FTIR microspectroscopy provides a useful tool for rapidly determining the pigment content of spores. In this paper, we use FTIR to detect a chemical response of spore wall UV-B absorbing pigments that correspond with levels of shade beneath the canopy of a high-latitude Swedish birch forest. A 27% reduction in UV-B flux beneath the canopy leads to a significant (p<0.05) 7.3% reduction in concentration of UV-B absorbing compounds in sporopollenin. The field data from this natural flux gradient in UV-B further support our earlier work on sporopollenin-based proxies derived from sedimentary records and herbaria collections.